1988
DOI: 10.1001/jama.1988.03410230064029
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Critical Care Physician Staffing on Patients With Septic Shock in a University Hospital Medical Intensive Care Unit

Abstract: To evaluate the effects of reorganizing physician resources in a medical intensive care unit (MICU), we studied the impact of these changes in patients with septic shock. Patients were compared during two consecutive 12-month periods: (1) an interval in which faculty without critical care medicine (CCM) training supervised the MICU (before CCM, n = 100) and (2) following staffing with physicians formally trained in CCM (after CCM, n = 112). Acute Physiology and Chronic Health Evaluation scores were utilized to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
59
0
6

Year Published

1996
1996
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 242 publications
(67 citation statements)
references
References 17 publications
2
59
0
6
Order By: Relevance
“…Thus, the admission by day of the week may be less likely to infl uence outcomes in critical care settings, a hypothesis that is supported by prior investigations. [21][22][23] Our study can be compared with prior investigations by Aujesky et al 12 and Bell and Redelmeier. 13 Aujesky et al 12 showed an adjusted OR of 1.17 (95% CI, 1.03-1.34) for mortality from PE on the weekend in a Pennsylvania health-care database from 2000 to 2002.…”
Section: Discussionmentioning
confidence: 64%
“…Thus, the admission by day of the week may be less likely to infl uence outcomes in critical care settings, a hypothesis that is supported by prior investigations. [21][22][23] Our study can be compared with prior investigations by Aujesky et al 12 and Bell and Redelmeier. 13 Aujesky et al 12 showed an adjusted OR of 1.17 (95% CI, 1.03-1.34) for mortality from PE on the weekend in a Pennsylvania health-care database from 2000 to 2002.…”
Section: Discussionmentioning
confidence: 64%
“…[4][5][6][7][8] At certain times of the day, the attending physician in the PICU may delegate the care of patients to a physician of at least the postgraduate year 2 level (in a level I PICU, this physician must be assigned to the PICU, and in a level II PICU, this physician must be available to the PICU) or to an advanced practice nurse or physician's assistant with specialized training in pediatric critical care. These nonphysician providers must receive credentials and privileges to provide care in the PICU only under the direction of the attending physician, and the credentialing process must be made in writing and approved by the medical director.…”
Section: Physician Staffmentioning
confidence: 99%
“…Staffing of these units with highly skilled nurses ensures optimal care and safety. Published literature documents the role of nurses' education and qualifications, and staffing ratios in improved patient outcomes (Aiken, Clarke, Cheung, Sloane, & Silber, 2003;Aiken, Clarke, Sloane, Sochalski, & Silber, 2002;Blegen, Goode, & Reed, 1998;Cho, Ketefian, Barkauskas, & Smith, 2003;Giraud et al, 1993;Lichtig, Knauf, & Milholland, 1999;McGillis Hall, Doran, & Pink, 2004;Needleman, Buerhaus, Mattke, Stewart, & Zelevinsky, 2002a;Needleman, Buerhaus, Mattke, Stewart, & Zelevinsky, 2002b;Person et al, 2004;Pronovost et al, 2001; Several studies have advocated for the physician intensivist model (Hanson et al, 1999;Pronovost et al, 2002;Reynolds, Haupt, Thill-Bahazorian, & Carlson, 1988) in ICUs. Durbin (2006), in advocating for care in ICUs through an intensivist-lead Team Model, pointed to an estimated 30% -50% reduction in mortality when intensivists rounded daily on critically ill patients, and to the shortening of the length of stay, reduction in cost, and prevention of complications with the implementation of this model.…”
Section: Haismentioning
confidence: 99%
“…Orders may be written by any licensed physician with privileges regardless of their specialty or training. The same year, Reynolds et al (1988) published the results of a retrospective study in which two different time periods were examined for the presence of a critical care-trained faculty in an ICU. Mortality was significantly decreased during the period following the supervision of critical care-trained faculty based on comparisons of severity of illness scores for the two time periods.…”
Section: Haismentioning
confidence: 99%
See 1 more Smart Citation